Variations of the Extent of Obstructive Coronary Artery Disease Among Canadian Immigrants - Hirmand Nouraei; Feng Qiu; Olivia Haldenby; Husam Abdel‐Qadir; Saswata Deb; Mina Madan; Baiju R. Shah; Maneesh Sud; Manav V. Vyas; Harindra C. Wijeysundera; Dennis T. Ko (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background An increasing proportion of immigrants are residing in developed countries, but little is known about the extent of their obstructive coronary artery disease (CAD). Our objective was to evaluate the association between immigrant status and CAD among immigrants. Methods and Results Initial coronary angiography performed for stable CAD from 2012 to 2021 in Ontario, Canada was examined. Immigrants were categorized by their country of birth into 7 world regions. The primary outcome was the rate of obstructive CAD, defined as the presence of left main stenosis ≥50% or major epicardial vessel stenosis ≥70%. Multivariable logistic regression analyses were conducted to compare the adjusted odds of obstructive CAD among long‐term residents and immigrants, and then within immigrant groups. Our cohort included 208 363 long‐term residents and 36 139 immigrants; the immigrants were substantially younger than the long‐term residents (61.3 versus 66.6 years). Male immigrants had 12.0% higher adjusted odds (95% CI, 1.17–1.24) of having obstructive CAD than long‐term residents, whereas no significant difference was observed among female immigrants and long‐term residents. There was also substantial variation in CAD among immigrants based on their country of origin. For example, male immigrants from South Asia had 49.0% higher adjusted odds of having CAD, whereas patients from Africa (0.75) and the Caribbean (0.63) had lower adjusted odds. Conclusions We observed earlier presentations for cardiac catheterization among immigrants with stable CAD and higher adjusted odds of having obstructive CAD among male immigrants compared with long‐term residents of Canada. Rates of obstructive CAD varied significantly by their region of birth.